2017
DOI: 10.3389/fmicb.2017.01063
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Secondary Metabolite Gene Clusters in Ophiostoma ulmi and Ophiostoma novo-ulmi Reveals a Fujikurin-Like Gene Cluster with a Putative Role in Infection

Abstract: The emergence of new microbial pathogens can result in destructive outbreaks, since their hosts have limited resistance and pathogens may be excessively aggressive. Described as the major ecological incident of the twentieth century, Dutch elm disease, caused by ascomycete fungi from the Ophiostoma genus, has caused a significant decline in elm tree populations (Ulmus sp.) in North America and Europe. Genome sequencing of the two main causative agents of Dutch elm disease (Ophiostoma ulmi and Ophiostoma novo-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 80 publications
0
26
0
1
Order By: Relevance
“…2009) on predicted protein databases (e-value < 1 × 10 −5 , query coverage > 60% and identity > 50% (Sbaraini et al . 2017).…”
Section: Methodsmentioning
confidence: 99%
“…2009) on predicted protein databases (e-value < 1 × 10 −5 , query coverage > 60% and identity > 50% (Sbaraini et al . 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The conservation of predicted SMCs among Verticillium spp. was assessed based on core enzyme conservation, using BLAST+ tool protein blast (blastp) (Camacho et al, 2009) on predicted protein databases (e-value < 1 x 10 -5 , query coverage > 60 % and identity > 50 % (Sbaraini et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In plant pathogenic fungi, secondary metabolites such as host-selective toxins are well known to play an important role in disease development ( Macheleidt et al., 2016 ). Bioinformatic annotations have identified O. novo-ulmi gene clusters putatively involved in biosynthesis of secondary metabolites, and interspecific comparative genomic analyses uncovered a fujikurin-like gene cluster (OpPKS8), found in the DED pathogens ( O. ulmi and O. novo-ulmi ) but absent in related non-phytopathogenic species ( Sbaraini et al., 2017 ). According to phylogenetic analyses the authors suggested that this toxin-related cluster may have been horizontally acquired by DED pathogens ( Sbaraini et al., 2017 ).…”
Section: Future Perspectives For Crispr/cas9 In Forest Pathologymentioning
confidence: 99%
“…Bioinformatic annotations have identified O. novo-ulmi gene clusters putatively involved in biosynthesis of secondary metabolites, and interspecific comparative genomic analyses uncovered a fujikurin-like gene cluster (OpPKS8), found in the DED pathogens ( O. ulmi and O. novo-ulmi ) but absent in related non-phytopathogenic species ( Sbaraini et al., 2017 ). According to phylogenetic analyses the authors suggested that this toxin-related cluster may have been horizontally acquired by DED pathogens ( Sbaraini et al., 2017 ). Genes in the OpPKS8 cluster are good candidates for exploration with CRISPR/Cas9, which could be used as an additional tool to elucidate the functions of this secondary metabolite cluster and its potential role in pathogenicity.…”
Section: Future Perspectives For Crispr/cas9 In Forest Pathologymentioning
confidence: 99%